Green synthesis of 2-aryl benzothiazole heterogenous catalyzed by MoO3 nanorods - Dighore Nitin R.; Anandgaonker Priyanka; Gaikwad Suresh T.; Rajbhoj Anjali S. (Green Processing and Synthesis, 2016)
The synthesis of MoO3 nanoparticles was done by the electrochemical method by using tetra butyl ammonium bromide (TBAB) as a stabilizer and structure directing agent in acetonitrile (ACN):tetrahydrofuran (THF) (4:1) solvent at a constant current supply of 18 mA/cm2. After heating the nanoparticles to 500°C in a muffle furnace, MoO3 nanorods were obtained. These synthesized MoO3 nanorods were characterized by UV-visible spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, powder X-ray diffraction (XRD) and scanning electron microscopy. The prepared nanorods were used as heterogeneous catalysts for the synthesis of 2-aryl benzothiazole derivatives. This protocol offers several advantages such as a green method, simple work-up procedure, recyclability of the catalyst and excellent product yield in a short reaction time.